Profitability Analysis of Bagda Farming in Some Selected Areas of Satkhira District (Progressive Agriculture, 2013)
This study aimed at examining the relative profitability of shrimp production in some areas of Satkhira district. Farm level data were collected through interviewing 60 randomly selected farmers. Mainly tabular analysis was done to achieve the major objectives of the study. Cobb-Douglas production function was used to estimate the contribution of key variables to the production process of shrimp farming. Analysis of costs and returns showed that per hectare total cost of shrimp production was Tk. 1,06,791.00 and net return from shrimp production was Tk. 84,023.80. Production function analysis proved that inputs such as fry, human labour, fertilizers, manure, lime etc. had positive impact on output. The study also identified some problems and suggested some possible steps to remove these problems. If these problems could be solved bagda production would possibly be increased remarkably in the study area as well as in Bangladesh.DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16874 Progress. Agric. 20(1 & 2): 221 229, 2009